Arbuscular Mycorrhizal Fungi Alleviate Drought Stress in Trifoliate Orange by Regulating H+-ATPase Activity and Gene Expression - Cheng, Hui-Qian; Zou, Ying-Ning; Wu, Qiang-Sheng; Kuča, Kamil (Frontiers in Plant Science, 2021)
A feature of arbuscular mycorrhiza is enhanced drought tolerance of host plants, while it is unclear whether host H+-ATPase activity and gene expression are involved in the physiological process. The present study aimed to investigate the effects of an arbuscular mycorrhizal fungus (AMF), Funneliformis mosseae, on H+-ATPase activity and gene expression of trifoliate orange (Poncirus trifoliata) seedlings subjected to well-watered and drought stress (DS), together with the changes in leaf gas exchange, root morphology, soil pH value, and ammonium content. Soil drought treatment dramatically increased H+-ATPase activity of leaf and root, and AMF inoculation further strengthened the increased effect. A plasma membrane H+-ATPase gene of trifoliate orange, PtAHA2 (MW239123), was cloned. The PtAHA2 expression was induced by mycorrhization in leaves and roots and also up-regulated by drought treatment in leaves of AMF-inoculated seedlings and in roots of AMF- and non-AMF-inoculated seedlings. And, the induced expression of PtAHA2 under mycorrhization was more prominent under DS than under well-watered. Mycorrhizal plants also showed greater photosynthetic rate, stomatal conductance, intercellular CO2 concentration, and transpiration rate and better root volume and diameter than non-mycorrhizal plants under DS. AMF inoculation significantly increased leaf and root ammonium content, especially under DS, whereas dramatically reduced soil pH value. In addition, H+-ATPase activity was significantly positively correlated with ammonium contents in leaves and roots, and root H+-ATPase activity was significantly negatively correlated with soil pH value. Our results concluded that AMF stimulated H+-ATPase activity and PtAHA2 gene expression in response to DS, which resulted in great nutrient (e.g. ammonium) uptake and root growth, as well as low soil pH microenvironment.